2021
DOI: 10.1093/infdis/jiab051
|View full text |Cite
|
Sign up to set email alerts
|

Projected HIV and Bacterial Sexually Transmitted Infection Incidence Following COVID-19–Related Sexual Distancing and Clinical Service Interruption

Abstract: Background The global COVID-19 pandemic has the potential to indirectly impact the transmission dynamics and prevention of HIV and other sexually transmitted infections (STI). It is unknown what combined impact reductions in sexual activity and interruptions in HIV/STI services will have on HIV/STI epidemic trajectories. Methods We adapted a model of HIV, gonorrhea, and chlamydia for a population of approximately 103,000 men … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 25 publications
5
66
0
1
Order By: Relevance
“…Modelling research has indicated that a decrease in sexual partnerships and interruption of clinical services over 18 months would reduce STI transmission. 22 Our analysis also suggested a reduction in unmet need for STI testing during lockdown compared with 2017. The shift from face-to-face testing to selfsampling is in line with findings of a rapid uptake in HIV hometesting among US MSM during social distancing.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Modelling research has indicated that a decrease in sexual partnerships and interruption of clinical services over 18 months would reduce STI transmission. 22 Our analysis also suggested a reduction in unmet need for STI testing during lockdown compared with 2017. The shift from face-to-face testing to selfsampling is in line with findings of a rapid uptake in HIV hometesting among US MSM during social distancing.…”
Section: Discussionmentioning
confidence: 60%
“…[17][18][19][20][21] However, our finding of a reduction in sexual activity with continued risk for HIV/STI transmission has been found elsewhere. 7 8 17-19 Other aspects of what may be described as COVID-19 'sexual distancing' 22 include increased use of phone sex, web cams and pornography, 8 18 20 and in our study, about one-sixth of participants had engaged in virtual sex since lockdown began.…”
Section: Discussionmentioning
confidence: 70%
“…Indeed, one study projected that long clinical service interruptions combined with a return to normal levels of sexual activity could result in thousands of excess STI cases over the next several years among MSM in Atlanta. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Social distancing and lockdown measures have led to decreased rates of diagnosis of syphilis in Rome and Madrid and syphilis and HIV in Taiwan compared to same time periods in previous years [76][77][78][79][80][81][82][83][84][85][86][87][88]. This phenomenon has also been noted in public health reports comparing 2020 data for HIV and syphilis in regions in Canada and in the USA [79,80]. It is unclear if the reduction is due to less frequent sexual encounters and a true decline in syphilis and HIV rates or if patients are postponing diagnosis and care leading to under-reporting as seen in other specialties.…”
Section: Covid-19 Hiv and Syphilismentioning
confidence: 99%